Poetry as Breath: Teaching Student Teachers to Breathe-Out Poetry (LEARNing Landscapes, 2010)
Poetry is a form of creative expression that exists to share a truth, an insight, or a feeling that enriches our humanity."Teaching" poetry requires us to be readers and writers of poetry ourselves. It requires that we are saying, "Poetry matters." I work with second-year student teachers in my Language Arts Methods class at McGill University to develop a passion for the poetic; to learn what Muriel Rukeyser refers to as breathing-in experience and breathing-out poetry. Using my own writing process and immersing my students in the genre, they begin to construct the complex understanding of why poetry matters and why that understanding is crucial to teaching it.
Keywords: poetry; creative expression; humanity; teaching poetry; reader; writer